1998
DOI: 10.1007/s004680050187
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of maximum photochemical efficiency in boreal Norway spruce stands

Abstract: The seasonal variation in maximum photochemical efficiency of photosystem II (F v /F m ) and the relationship between F v /F m and climatic factors such as irradiance, frost-nights and daily mean temperature was studied in young Norway spruce trees for 4 years in northern Sweden. As a result of night frost, the F v /F m -ratio gradually decreased during the autumn. There was between-year variation in the pattern of F v /F m in fully exposed shoots during autumn and spring, largely as an effect of differing tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 21 publications
2
40
0
Order By: Relevance
“…The seasonal variations of the Chl a+b and fluorescence parameters correlated well with earlier reports in the photosynthetic performance for Scots pine or other pine trees (Linder 1972, Martin et al 1978, Leverenz and Öquist 1987, Wang 1996, Lundmark et al 1998. They exhibited a gradual decline during late summer and autumn, marked inhibition during the winter, and a rapid recovery in early spring.…”
Section: Discussionsupporting
confidence: 88%
“…The seasonal variations of the Chl a+b and fluorescence parameters correlated well with earlier reports in the photosynthetic performance for Scots pine or other pine trees (Linder 1972, Martin et al 1978, Leverenz and Öquist 1987, Wang 1996, Lundmark et al 1998. They exhibited a gradual decline during late summer and autumn, marked inhibition during the winter, and a rapid recovery in early spring.…”
Section: Discussionsupporting
confidence: 88%
“…This could be expected, because a temperature sum is irreversible by nature whereas the recovery of photosynthesis in a coniferous forest is not. Depending on the fluctuations in air temperature, the recovery of photosynthesis of evergreen species in winter and spring can begin, be reversed and begin again [Kramer and Kozlowski, 1979;Schaberg et al, 1995;Lundmark et al, 1998]. Therefore, winter photosynthesis and, finally, OEGS are related to reversible temperature-dependent variables such as one-day or five-day average temperature [Lundmark et al, 1998;Schaberg et al, 1995]; an irreversible variable, such as a temperature sum, could be better connected with irreversible phenological processes such as bud break.…”
Section: Discussionmentioning
confidence: 99%
“…According to Hollinger et al [1999], the carbon exchange rates of a spruce-dominated forest in Maine, USA decreased at the time of the first frost. Furthermore, Lundmark et al [1998] found that the maximum photochemical efficiency of photosystem II in young Norway spruce trees gradually decreased because of night frosts in autumn, and Hällgren et al [1990] reported a 30-50% inhibition of the light-saturated rate of CO 2 assimilation after cold nights with minimum temperatures between À4 and À6°C. Vogg et al [1998] showed that also the shortening day length decreases the photosynthetic rates of Scots pine trees and that this effect is independent of temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Climate transitions between the winter and spring exert a principal control over the photosynthetic dynamics of coniferous forest ecosystems (Troeng and Linder 1982;Leverenz and Ö quist 1987;Lundmark et al 1998;Law et al 2000;Lloyd et al 2002;Monson et al 2002;Huxman et al 2003;Tanja et al 2003;Ensminger et al 2004). One of the advantages of the evergreen coniferous growth form is the rapid upregulation of photosynthetic activities during the spring warm-up, which allows trees to capitalize quickly on favorable weather conditions.…”
Section: Introductionmentioning
confidence: 96%